Antibiotic use and associated factors in adult outpatients from 2000 to 2019. Issue 6 (19th October 2021) - Franchi, Carlotta; Mandelli, Sara; Fortino, Ida; Nobili, Alessandro
Abstract: The aims of the study were to assess the changes in 19‐years use of antibiotics (overall, by age, sex and geographical area) and of those classes deemed to be quality indicators for their consumption and to evaluate factors associated to antibiotic use. We analyzed drug prescription data collected in the administrative database of the Lombardy Region (Northern Italy) for outpatients aged 40+ years from 2000 to 2019. Logistic regression analyses were performed to evaluate the association between receiving at least one antibiotic prescription and year of observation, gender, age groups, area of residence, polypharmacy and hospitalizations in the index year. The prevalence of patients prescribed with antibiotics remained high from 2000 (33.8%) to 2019 (32.6%). Prevalence of use of second‐line choice antibiotics (penicillin combinations with beta‐lactamase inhibitors, third and fourth generation cephalosporins, macrolides) continued to increase, only fluoroquinolones decreased in 2019 (19%) comparing to 2018 (26%), at the time when the Italian Medicines Agency promulgated safety warnings. Females (OR 1.28, 95%CI 1.27–1.28), people living in Brescia (OR 1.24, 95%CI 1.24–1.25), those exposed to polypharmacy (OR 2.57, 95%CI 2.56–2.57) and those hospitalized 1 to 3 (OR 1.86, 95%CI 1.85–1.86) or more than 3 (OR 2.02, 95%CI 2.01–2.03) times a year had a statistically significant higher risk of receiving antibiotics. The high use of antibiotics over the study period further reinforces the need of impactful interventions, in order to improve the rational use of antibiotics and to reduce the risks of antimicrobial resistance. The differences outlined should be considered when monitoring and planning these interventions. Abstract : We analyzed drug prescription data collected in the administrative database of the Lombardy Region (Northern Italy) for outpatients aged 40+ years from 2000 to 2019, in order to assess the changes in the use of antibiotics and of those classes deemed to be quality indicators for their consumption and to evaluate factors associated to antibiotic use. The prevalence of patients prescribed with antibiotics remained high from 2000 (33.8%) to 2019 (32.6%). Prevalence of use of second‐line choice antibiotics (penicillin combinations with beta‐lactamase inhibitors, third and fourth generation cephalosporins, macrolides) continued to increase, only fluoroquinolones decreased in 2019 (19%) comparing to 2018 (26%), at the time when the Italian Medicines Agency promulgated safety warnings.